(untitled) (Bangladesh Journal of Botany, 2023)
Cytospora species are found in Xinjiang with stem canker disease. Cytospora species were identified based on morphological characteristics and molecular biology from economic forests and shelter belt in Xinjiang. A total of 281 isolates were obtained from woods canker of 17 hosts in Xinjiang. The strains identified were Valsa mali (anamorph: Cytospora sacculus), Valsa sordida (anamorph: Cytospora chrysosperma), Valsa macolica (anamorph: Cytospora schulzeri), Leucostoma niveum (anamorph: Cytospora nivea) and Cryptosphaeria pullmanensis (anamorph: Cytosporina pullmanensis). The V. mali and V. sordida wwere the main pathogens of economic forest and shelter forest, respectively. It is also hoped that this will lead to improve management strategies for diseases associated with these fungi. Bangladesh J. Bot. 51(4): 1029-1037, 2022 (December) Special